Construção de um sistema de filtração de gases para o estudo da formação e remoção de tortas de filtração - Nunes, Deivid Marques (2011)
The studies developed in this work aimed to build an experimental gas filtration unit and also study the formation and the removal of filter cakes in different filter media (polypropylene, polyester and acrylic) provided by Gino Cacciari Ltda., a company from São Paulo, Brazil. The particulate matter used in this study was a concentrated phosphate, provided by FOSFERTIL, a company from Patos de Minas, Brazil. The density of this material is 3 2,89 0,009g / cm , and its volume average diameter is 12,72m . The filtration system was built with five components, namely, a filtration box, with a filtration area of 314,16 cm2; a power feeding system with controlled humidity; manometers; compressed air lines; and a blower. The filtration experiments were performed in each fibrous filter, with three different superficial filtration velocities of 5, 7,5 e 10 cm/s, for each of the four established maximum pressure drop, which values were 10, 20, 30 and 40cmH2O. To remove the filter cakes, the reverse air flow mechanism was used with a cleaning velocity of 15 cm/s. The experiments were carried out aiming to verify the performance of the filter media in the formation and removal of filter cakes, according to the variation of the maximum pressure drop and the filtration velocity. Thus, it was possible to determine filter cakes porosity for each fibrous filter. The results showed that acrylic was the filter which presented an opener surface structure and a higher permeability, followed by polyester and polypropylene. For the four established maximum pressure drops, the difference of the filter media structure afforded a higher collection of particles in the acrylic, the most permeable filter. For the three velocities studied, that difference afforded a longer period of internal filtration, what did not happen to polypropylene, in which the superficial filtration prevailed. The amounts of retained mass and removed mass were larger in the acrylic, followed by polyester and polypropylene. Besides, the amount of retained mass was larger when filtration velocities were higher. Filter cake porosity was reduced as the result of the increased thickness of the cakes (increase in the established pressure drop) and then it started to increase again. The acrylic, the most permeable filter medium, presented more porous and less resistant cakes. At least, in the equations used in this study, the quadratic term in Ergun and MacDonald equations was negligible. The equations of MacDonald and Kozeny-Carman presented higher porosity values when compared to Ergun equations (1952) and modified Ergun equation, and the porosity variation was higher for acrylic (0,33 - 0,39), followed by polyester (0,34 - 0,43) and polypropylene (0,36 - 0,48).